Rocking the earthquake reportage a study on Rappler's coverage of earthquakes that hit the Philippines from 2012-2017 - Vargas, Mariel Amor Serrano (University of the Philippines Diliman, 2018)
"As the threat of a destructive earthquake looms in the Philippines, the role of the media as the general public's educators warrants an examination. Have they been doing enough to inculcate earthwuake preparedness in every individual and/or family? Have they been reporting with excellence so as to minimize the loss of lives brought about by inadequate information about earthquake-related disasters? This thesis looked at digital news site Rappler's reportage of earthquakes that struck the Philippines since 2012 until 2017. This research examined how much information regarding earthquake preparedness was fed to the public, how science and emotions were incorporated in the coverage, how technological tools provided by the online medium were utilized, and how Rappler's coverage of anything earthquake-related has changed through the years."